Metabolic effects of preexposure prophylaxis with coformulated tenofovir disoproxil fumarate and emtricitabine - David V. Glidden (2018)
© The Author(s) 2018. Published by Oxford University Press for the Infectious Diseases Society of America. Background Antiretroviral drugs have been associated with changes in lipids, fat mass and dat distribution. Tenofovir disoproxil fumarate (TDF) has been shown to have a more favorable metabolic profile than other drugs in its class. However, the metabolic effects of TDF in preexposure prophylaxis (PrEP) are unknown. Methods We evaluated the effects of TDF/emtricitabine (FTC) on lipids and body composition in a blinded, placebo-controlled PrEP trial. Participants enrolled in a metabolic subcohort (N = 251, TDF/FTC; N = 247, placebo) consented to fasting lipid panels, dual-energy X-ray absorptiometry scans for body composition, and pharmacologic testing of drug metabolites at baseline and every 24 weeks thereafter. Results Lean body mass was stable and unaffected by TDF/FTC. Body weight increased in both groups but was lower on TDF/FTC through week 72. This difference was explained by lower fat accumulation on TDF/FTC. The net median percent difference (standard error, P value) for TDF/FTC vs placebo at week 24 was -0.8% (0.4%, P =.02),+0.3% (0.4%, P =.46), and -3.8% (1.4%, P =.009) for total, lean, and fat mass, respectively. There was no apparent differential regional fat accumulation on TDF/FTC. Decreases in cholesterol, but not triglycerides, were seen in TDF/FTC participants, with detectable drug levels compared to placebo. Conclusions TDF/FTC for PrEP showed cholesterol reductions and appeared to transiently suppress the accumulation of weight and body fat compared to placebo. There was no evidence of altered fat distribution or lipodystrophy during daily oral TDF/FTC PrEP.